Penggunaan Aplikasi Excel Sebagai Aplikasi Pembantu SIMRS Gos Dalam Pencatatan Dan Pelaporan Di Rumah Sakit TNI AU Soewondo RSAU Dr. Abdul Malik - Sitorus, Mei Sryendang; Simanjuntak, Esraida; Lubis, Siti Permata Sari; Hutasoit, Theresia; Sihite, Geovani Arta; Harefa, Calvin Natana Eli; Yani, Fitri (Jurnal ABDIMAS Budi Darma, 2024)
The Hospital Management Information System (SIMRS) is a vital component in hospital operations to ensure the efficiency of recording and reporting medical and administrative data. This research aims to analyze the use of the Microsoft Excel application as an auxiliary application in supporting SIMRS Gos at the Soewondo TNI AU Hospital RSAU Dr. Abdul Malik. The use of Excel aims to increase the speed and accuracy of recording and reporting hospital data which has not been fully accommodated by SIMRS Gos. The research method used is a qualitative descriptive approach with interviews and direct observation of hospital officers involved in the recording and reporting process. The research results show that the Excel application provides flexibility in processing data, but requires increased integration with SIMRS to minimize data input errors and duplication of work. The recommendation from this research is further development of SIMRS so that it can accommodate the functions currently carried out by Excel, in order to increase work efficiency and data accuracy in hospitals